Examining appropriate diagnosis and treatment of malaria: availability and use of rapid diagnostic tests and artemisinin-based combination therapy in public and private health facilities in south east Nigeria - Uzochukwu Benjamin SC; Chiegboka Lausdeus O; Enwereuzo Chibuike; Nwosu Usonwanne; Okorafor David; Onwujekwe Obinna E; Uguru Nkoli P; Sibeudu Florence T; Ezeoke Ogochukwu P (BMC, 2010)
Abstract Background Rapid diagnostic tests (RDTs) and Artemisinin-based combination therapy (ACT) have been widely advocated by government and the international community as cost-effective tools for diagnosis and treatment of malaria. ACTs are now the first line treatment drug for malaria in Nigeria and RDTs have been introduced by the government to bridge the existing gaps in proper diagnosis. However, it is not known how readily available these RDTs and ACTs are in public and private health facilities and whether health workers are actually using them. Hence, this study investigated the levels of availability and use of RDTs and ACTs in these facilities. Methods The study was undertaken in Enugu state, southeast Nigeria in March 2009. Data was collected from heads of 74 public and private health facilities on the availability and use of RDTs and ACTs. Also, the availability of RDTs and the types of ACTs that were available in the facilities were documented. Results Only 31.1% of the health facilities used RDTs to diagnose malaria. The majority used the syndromic approach. However, 61.1% of healthcare providers were aware of RDTs. RDTs were available in 53.3% of the facilities. Public health facilities and health facilities in the urban areas were using RDTs more and these were mainly bought from pharmacy shops and supplied by NGOs. The main reasons given for non use are unreliability of RDTs, supply issues, costs, preference for other methods of diagnosis and providers' ignorance. ACTs were the drug of choice for most public health facilities and the drugs were readily available in these facilities. Conclusion Although many providers were knowledgeable about RDTs, not many facilities used it. ACTS were readily available and used in public but not private health facilities. However, the reported use of ACTs with limited proper diagnosis implies that there could be high incidence of inappropriate case management of malaria which can also increase the economic burden of illnesses. Government and donors should ensure constant availability of RDTs in both public and private facilities, so that every treatment with ACTs is accompanied with proper diagnosis.